Frequency of in-Stent Restenosis in patients having DES, with Stent Length Greater than 30mm Presenting to Tertiary Care Center - Muhammad Ahmad Raza Butt, Bakht Umar Khan, Muhammad Saeed Afridi, Muhammad Suleman Khan, Mujeebullah Tareen, Abdul Hadi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to calculate the incidence of in-stent restenosis in patients with DES and stent lengths higher than 30mm who presented to a tertiary care hospital. Study Design: A Cross-sectional study Place and Duration: This cross-sectional study was conducted at Department of Cardiology, Rashid Latif Medical College, Lahore in the duration from February, 2022 to July, 2022. Methods: There were 83 patients of coronary artery disease (CAD)were included. After obtaining written consent from participants, researchers collected information about their participants' ages, sexes, body mass indexes, and co-morbidities. Atherosclerosis risk variables were collected with baseline investigations and an echocardiography for ejection fraction determination. Imaging studies were reviewed by board-certified interventional cardiologists, who found evidence of ISR. Past angioplasty information and stent details were recorded. Results: In our study mean age of the presented cases was 54.13±7.44 years and mean BMI 25.2±13.87 kg/m2. Most common comorbidity was diabetes found in 25 (30.1%) followed by hypertension in 23 (27.7%) and dyslipidemia in 20 (24.1%) cases. We found that 40 (48.2%) patients were smokers. Mean LDL cholesterol of the patients was 68.6±1.97 mg/dl and mean uric acid was 6.2±2.35 mg/dl. Majority of the cases 45 (54.2%) had poor socio-economic status. We found that frequency of ISR was higher among cases of biomatrix stent 24 (28.9%), followed by Xience stent in 22 (26.5%) cases, Ultimaster stent in 19 (22.9%) and Xlimus stent in 18 (21.7%) cases after coronary angiograpghy. Our results showed that the stents longer than 30mm were associated with a higher incidence of In-Stent Restenosis (p=0.03). Conclusion: Based on the findings of this study, we came to the conclusion that a previous diagnosis of diabetes mellitus and a longer stent length are both significant risk factors for developing in-stent restenosis. In our research, we found that instances with biomatrix stents had a greater incidence of ISR. Keywords: CAD, Drug eluting stents (DES), Coronary angiography, In-Stent Restenosis